Design and experimentation of a modeling sequence to reveal function ideas - Soria Pérez, Alejandra; Alvarado Monroy, Angelina; Pacheco Juárez, Yaziel (IE Revista de Investigación Educativa de la REDIECH, 2024)
The design and experimentation of a modeling sequence are presented to reveal ideas and relationships that arise from students when representing the development of singing talent in a group of people over a period of time. The experimentation was carried out with 37 students (18 years old) in a leveling course previous to entry into a degree in Mathematics, following the design-based research methodology, completing a prospective analysis, classroom experimentation, and redesign assessment cycle. Emerging categories were identified from an inductive analysis to classify the students’ representation models: linear, piecewise linear, smooth, discrete, and alternative. The results show that the students used both their prior knowledge and the insights gained during team interactions to represent the characters’ stories and illustrate the development of talent over a period of time. Additionally, it was notorious that to depict crucial moments, the students explored the characters’ behavior around these.